Rancang Bangun Aplikasi Sistem Pemesanan Minyak Pelumas (Studi Pada Pt. Xyz) - Sinta Rukiastiandari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
The booking system lubricating oil at Pt. Xyz is currently using the system is recording data konvensianal lubricant conducted in units Means. The system runs has many drawbacks dianataranya allow for mistakes, takes a long time in the search process data and the reporting process. Based on the above problems, the authors want to do research to build applications Grease Openness Booking online.This application is built using ASP, consisting of the order data (penjadawalan) of oil to produce booking reports oil depot locations and Support Unit. In addition to using ASP programming language ordering application system lubricating oils also use tools for typing noteped ASP, and Microsoft Office Access database for writing, Mozilla Firefox as a browser, Microsoft paint for image editing.